Effect of Sports Energy Drink on Fat Metabolism and Weight Loss of College Students - Huan Chu; Wenyong Zhou; Shanshan Wang (Journal of Food Quality)
In order to solve the problem of fat metabolism and weight loss of college students, this paper puts forward a problem of the influence of sports energy drinks. Energy drink is a combination of sports drinks, energy drinks, and other special functional drinks (such as nutrient drinks with added vitamins and minerals; herbal drinks with Chinese herbal ingredients), a general term for a large category of drinks that provide specific health and nutritional functions for special groups of people. With the continuous improvement of people's consumption level and their constant attention to their own health, the consumption of energy drinks is also increasing. Energy drinks have become a new generation of drinks after carbonated drinks, drinking water, fruit and vegetable juice, and tea. At present, the total annual output of beverages in the world exceeds 300 billion liters, and functional beverages have become the fastest growing beverage varieties. Fat is the main energy supply material for endurance sports. The catabolism of fat during sports is the key link for the body to obtain energy. For the general population, abnormal fat metabolism is the main cause of obesity. In this paper, 10 healthy male and female college students without training experience were used to determine the maximum fat metabolism intensity FATmax. Based on this, the exercise prescription of maximum fat oxidation intensity for 8 weeks was formulated. The functional ability, maximum oxygen uptake, body fat percentage, quiet heart rate, blood pressure, and vital capacity before and after the experiment were measured to observe the exercise effect. The fitness effect of maximum fat metabolism intensity was studied to provide theoretical support for college students’ fitness exercise. The study found that there was no significant difference between boys and girls in the maximum fat oxidation rate and FATmax, and girls’ E. C. and running speed corresponding to FATmax were significantly lower than those of boys. After 8 weeks of exercise prescription exercise of maximum fat metabolism intensity, the E. C. and maximum oxygen uptake of boys and girls increased significantly; quiet heart rate, vital capacity index, and body fat percentage were significantly improved; and the changes in girls were more significant than boys. The results show that there is no gender difference in FATmax. The corresponding exercise intensity (7.22 METs for boys and 5.25 METs for girls) and running speed (9.73 km/h for boys and 8.65 km/h for girls) can be used as a reference for formulating college students’ fitness exercise prescriptions. The fitness exercise prescription based on FATmax can improve cardiopulmonary function and body composition, especially for girls. FATmax can be used as a reference standard for formulating fitness exercise prescriptions.